Town – Village: Dichotomy Or Continuum? Reflections In Three Contexts: Sociological, Economic And Geographical (Research Bulletins of the Faculty of Economic Sciences, 2017)
The town and the village are two subsystems that are mutually complementary and contradictory at the same time, since in socio-economic macrosystem they produce both types of connections. From the socio-economic development point of view of socio-economic development, urban and rural areas constitute a whole, however, as a result of the ambiguity of the relationship between them we are still looking for an answer to the question where the town ends and the village begins? Reflections on the interpretation of so defined research problem, have been presented in three dimensions: spatial, sociological and economic.The methodological dilemma examined in the article, which concerns the determination of the relationship between town and village, is ultimately unsolvable. Opposing town to village has a historical dimension, as is has been present ever since towns exist. Its formulation, at first dichotomous, then in relationship of rural – urban continuum, has evolved along with the role which agriculture played in the economy. In the current phase it has been generalized in the form of center – periphery opposition.
Keywords: town – village relationship; dichotomy; continuum; center – periphery